2023
DOI: 10.1063/5.0132172
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbolic metamaterial nanoparticles random array for thermoplasmonics in the II and III near-infrared windows

Abstract: Plasmonic nanostructures capable of converting light to heat have found wide applications, thus giving rise to the field of thermoplasmonics. Among them, the use of gold-based plasmonic structures in near-infrared (NIR) spectral regions has catalyzed substantial research efforts due to the potential impact in clinical therapy applications. However, the photon scattering effect scaling with the square of the nanoparticle volume leads to high scattering and then low absorption efficiency. This limit has hindered… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…However, when the ambient temperature surrounding the structure increases, the refractive index of the meta-antenna changes and thus also the way these structures can interact with light, in particular how they absorb radiation (Figure b). The main reason for this change is connected to the fact that the metal building block of our meta-antennas is sensitive to temperature changes, and this sensitivity is amplified by the fact that light–matter interactions at the nonradiative mode are greatly increased. ,, Moreover, the size of the antennas increases due to thermal expansion, which in turn lowers the electron density, and thus the plasma frequency, causing a change in the Au permittivity. With rising temperature, a decrease of the effective mass has been shown to counteract the effect of the lower electron density on the plasma frequency of thin Au films, causing the plasma frequency to increase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when the ambient temperature surrounding the structure increases, the refractive index of the meta-antenna changes and thus also the way these structures can interact with light, in particular how they absorb radiation (Figure b). The main reason for this change is connected to the fact that the metal building block of our meta-antennas is sensitive to temperature changes, and this sensitivity is amplified by the fact that light–matter interactions at the nonradiative mode are greatly increased. ,, Moreover, the size of the antennas increases due to thermal expansion, which in turn lowers the electron density, and thus the plasma frequency, causing a change in the Au permittivity. With rising temperature, a decrease of the effective mass has been shown to counteract the effect of the lower electron density on the plasma frequency of thin Au films, causing the plasma frequency to increase.…”
Section: Resultsmentioning
confidence: 99%
“…36−38 In addition, metal−insulator multilayers display hyperbolic optical dispersion, 39,40 and thanks to this property they have successfully been implemented as negative index materials 41−43 and superabsorbers driving resonant gain singularities, 44−47 as well as for hot-electron generation and manipulation, 48,49 super resolution imaging, 50 ultracompact optical quantum circuits, 51 and lasing. 52 In this context, it has been shown that multilayered metaldielectric antennas displaying hyperbolic dispersion have two separated radiative and nonradiative channels 19 and that this property can be exploited to manipulate electron dynamics on ultrafast time scales 49 as well as for practical applications such as localized hyperthermia 53 and enhanced spectroscopy. 21 The unique property of having two separated spectral regions where either a radiative or a nonradiative process is dominating on the other, and vice versa, can open plenty of opportunities in developing multifunctional systems which can behave at the same time as optimal scatterers and absorbers.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include designing novel hybrid nanodevices and hyperbolic metamaterials with enhanced optical properties and sensing performances. [89][90][91][92][93] In particular, the plasmonic properties and sensing performances of metallic nanostructures can be hugely enhanced by designing hybrid magneto-plasmonic nanostructures. [94,95] As a result, magneto-optical plasmonic heterostructures with ultranarrow resonances have been widely employed for sensing applications.…”
Section: Magneto-plasmonic Heterostructure Sensorsmentioning
confidence: 99%
“…After the development of femtosecond lasers for the generation of ultrashort light pulses 20,21 , it became clear that we can use such technology to drive ultrafast electronic processes at the nanoscale, including plasmonic excitations [22][23][24][25][26][27][28] . In this context, heterojunctions of metals and dielectric materials allow a lot of possibilities for the manipulation and exploitation of light-matter interactions, including ultrafast hot electrons dynamics, magnetooptical effects and nonlinear optical processes 18,[29][30][31][32][33][34][35][36][37][38] . In particular, if the dielectric material is replaced by a semiconducting transition metal dichalcogenide (TMD), we can further boost the control of nanoscale optical excitations [39][40][41][42] , including plasmonic-induced charge injection [43][44][45][46][47][48] , as well as enhance charge dynamics in transistors 49 and photovoltaic devices 50 .…”
Section: Introductionmentioning
confidence: 99%